2020
DOI: 10.12659/msm.918883
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Improves Fibrosis-Induced Abnormalities in Atrial Conduction and Vulnerability to Atrial Fibrillation in Chronic Intermittent Hypoxia Rats

Abstract: Background: The structural remodeling of atrial architecture, especially increased amounts of fibrosis, is a critical substrate to atrial fibrillation (AF). Doxycycline (Doxy) has recently been shown to exert protective effects against fibrogenic response. This study investigated whether doxycycline (Doxy) can sufficiently ameliorate the fibrosis-induced changes of atrial conduction and AF vulnerability in a chronic intermittent hypoxia (CIH) rat model. Material/Methods: Sixty rats were randomized into 3 group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…However, due to its wide range of nonantibiotic properties and relative safety profile, extensive pre-clinical and clinical studies have been investigating doxycycline therapeutic approaches, with promising results. Reports in several medical settings have shown ameliorating the severity of diabetic retinopathy [ 44 ] and proliferative vitreoretinopathy [ 45 ], inhibiting the proliferation and proapoptotic effect in human cancer cells [ 46 , 47 , 48 , 49 ], positive effects on osteoarthritis and posttraumatic arthritis progression [ 50 ], and reduction of cardiac dysfunction in different models of heart damage [ 22 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to its wide range of nonantibiotic properties and relative safety profile, extensive pre-clinical and clinical studies have been investigating doxycycline therapeutic approaches, with promising results. Reports in several medical settings have shown ameliorating the severity of diabetic retinopathy [ 44 ] and proliferative vitreoretinopathy [ 45 ], inhibiting the proliferation and proapoptotic effect in human cancer cells [ 46 , 47 , 48 , 49 ], positive effects on osteoarthritis and posttraumatic arthritis progression [ 50 ], and reduction of cardiac dysfunction in different models of heart damage [ 22 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that patients with OSA are vulnerable to the incidence of AF [24,25]. CIH, which is a hallmark of OSA, has been associated with the development of brosis in multiple tissues, including the myocardium [20,26], systemic vasculature [27], liver [28], and lungs [29]. Intermittent hypoxia for a period as short as 4-5 weeks can cause diffuse collagen ber deposition in rats [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The rats were allowed free access to food and water and provided with a normal diet. The atrial brosis rat model was established by exposure to a CIH environment, using a previously described protocol [20]. Brie y, the rats in the CIH group were placed in a chamber lled with alternating cycles of nitrogen and oxygen, whereas the control group rats were maintained under normal oxygen conditions.…”
Section: Construction Of a Cih-induced Rat Modelmentioning
confidence: 99%
“…Atrial fibrillation (AF) is one of the most frequent forms of human arrhythmias, with a significant disability and fatality rate in patients. 393,396,397 The etiology of AF is linked to MMP-9; the increased activity of MMP-9 causes atrial fibrosis and induces AF. 398 Another study demonstrated that HIF-1α stimulates the downstream factor TGF-ÎČ1 by promoting the expression of angiotensin II (Ang II), which causes high expression of MMP-9.…”
Section: Hypoxia In Arrhythmiamentioning
confidence: 99%